Career intentions and choices of paediatricians entering training in the UK. Issue 6 (23rd December 2014) - Shortland, David; Roland, Damian; Lumsden, Daniel Edward; Ewing, Carol; L'Esperance, Veline; McColgan, Martin; Winch, Rachel; Mahmood, Shazia
Abstract : Introduction: The paediatric workforce has grown substantially in recent years. Roles have changed considerably with the introduction of working time legislation and a move towards a trained doctor solution. By gaining a better understanding of paediatric trainees' career intentions, this study aims to assess whether the right workforce is being trained to meet the future demand for paediatric services in the UK. Method: A survey was sent to paediatric specialist trainees, when they were expected to have completed their 1st year of Specialty Training or Fixed Term Specialty Training Appointments, in 2009 (part 1). A second survey was sent to the same cohort when they were expected to have completed their 3rd year in 2011 (part 2). Results: In part 1 of the survey, the response rate was 79.1%. In part 2 the response rate was 80.5%. Of those who had responded to part 1, 87.4% also responded to part 2. The attrition rate of trainees leaving the paediatric training scheme between the 1st year and 3rd year of training was 15%. Of those still training in paediatrics after the 3rd year, 38.7% intended to be subspecialty paediatricians, 25.7% general paediatricians, 5.4% community paediatricians and 3.5% academic paediatricians. 26% were undecided and 0.6% did not intend to follow a career in paediatrics at all. The proportion of trainees who were undecided about their career intentions had risen substantially from 7.7% after the 1st year. There was a decrease in trainees' confidence in obtaining a consultant post between the 1st year and the 3rd year. Conclusions: Workforce planning is a complex task and this study shows that trainees will change their career plans while progressing through their run-through programmes. A better understanding of these factors will enable the Royal College of Paediatrics and Chld Health to deliver the right workforce for the UK.